Numerical Simulation of the Flow Field Characteristic of Lubricating Oil in the Gearbox of High Speed Locomotive - Liu Zhongling; Fan Naize; Tian Huajun; Zhao Jiadong; Ning Ke; Pei Bang; Li Baokui; Zhang Xiangru; Xu Hui (Jixie chuandong)
The dynamic numerical simulation of inner oil bath lubrication flow filed of a type locomotive gearbox is carried out by using dynamic mesh and Profile technology based on CFD software Fluent. A two- dimensional VOF multiphase model of the gearbox is built,the dynamic characteristic of the inner flow filed is calculated as the input velocity of the gearbox varied during the 3 speed（ starting at low speed,medium speed,maximum speed）. The phase,pressure and velocity distribution of internal flow field of the gearbox under different speed condition are obtained. The simulation results would provide a theoretical basis for the design and maintenance of the gearbox.